KSHV‐TK is a tyrosine kinase that disrupts focal adhesions and induces Rho‐mediated cell contraction. (3rd December 2014) - Gill, Michael B; Turner, Rachel; Stevenson, Philip G; Way, Michael
<x xml:space="preserve">Abstract</x> Gammaherpesviruses are known to encode very inefficient thymidine kinases. KSHV thymidine kinase is actually a tyrosine kinase that induces focal adhesion disassembly via its interaction with known regulators including members of the Crk‐related family of adaptor proteins. <boxed-text content-type="graphic" id="embj201490358-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text>